Diagnosis of neonatal neurofibromatosis type 1: a case report and review of the literature - Qiuying Zheng; Bei Xia; Xiaoli Zhao; Ruijie Wang; Fusui Xie; Nihui Pei; Hongwei Tao; Tingting Ding; Lei Liu (BMC, 2023)
Abstract Background Neurofibromatosis Type 1 (NF1) is a rare genetic disorder characterized with the development of multiple benign tumors on the nerves and skin. Case presentation This report described a neonatal case with a large mass observed on the left side of the maxillofacial and cervical region at birth. Meantime, multiple cafe-au-lait macules (CALMs) were seen on the trunk and both lower extremities. Conclusions In this case, the clinical features of the rare NF1 neonate are discussed along with its ultrasound findings.